Modeling the ionospheric impact of tsunami‐driven gravity waves with SAMI3: Conjugate effects. Issue 14 (27th July 2015) - Huba, J. D.; Drob, D. P.; Wu, T.‐W.; Makela, J. J.
Abstract The Naval Research Laboratory first‐principles ionosphere model SAMI3 is used to study the ionospheric effects associated with tsunami‐driven gravity waves. Specifically, the Tohoku‐Oki tsunami of 11 March 2011 is modeled. It is shown that gravity wave‐induced variations in the neutral wind lead to plasma velocity variations both perpendicular and parallel to the geomagnetic field. Moreover, the electric field induced by the neutral wind perturbations can map to the conjugate hemisphere. Thus, electron density variations can be generated in both hemispheres which impact the total electron content (TEC) and 6300 Å airglow emission. It is found that the TEC exhibits variations of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2cr24dhw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />≲±0.1</alternatives> total electron content unit (1 TECU = 1016 el m−2) and the 6300 Å airglow emission variation is up to ∼±2.5% relative to the unperturbed background airglow.